2002
DOI: 10.12968/hosp.2002.63.1.1723
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and renal stones: management and treatment

Abstract: The prevalence of renal tract calculi in the population is such that patients may present acutely not only to urologists, but in the setting of any medical specialty. This article aims to enable all practitioners to be able to recognize the condition and instigate early investigation and management before referring to the urologist for definitive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The treatment and management of stones have been comprehensively reviewed elsewhere (11,12). Knowledge of the type of precipitant may aid in the prediction of the type of stones likely to be formed and therefore help with selection of the most appropriate treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment and management of stones have been comprehensively reviewed elsewhere (11,12). Knowledge of the type of precipitant may aid in the prediction of the type of stones likely to be formed and therefore help with selection of the most appropriate treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The stone removal could be done with open or endoscopic techniques. [21] In review of literature, most of cases stone was managed by transvesical suprapubic open cystolithotomy or by transvaginal route with chisel and hammer or forceps. [2,9,19,22,23,24] Dalela et al [2] suggested stone could be removed endoscopic cystolithotripsy which can prevent unnecessary trauma to the ureter and extension of the fistula tract by forceful traction applied during open methods of stone retrieval.…”
Section: Casementioning
confidence: 99%